INTERVAL TYPE-2 FUZZY MODEL FOR CUSTOMER COMPLAINT HANDLING - RAZALI, RAZULAIMI (2018)
Complaint management system (CMS) has become increasingly important for organizations, businesses, and government in Malaysia. The interaction between customers and business provider based on complaints which referring to perceptions and wording involves uncertainties and not an easy task in complaint handling process to rank the complaint.